Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Motivasi Belajar Peserta Didik Pada Materi Sistem Persamaan Liner Dua Variabel (SPLDV) di Kelas VIII A SMP Negeri 4 Tasik Putri Puyu Syafruddin Perwira Negara - Syafruddin Perwira Negara (Journal on Education, 2021)
This study aims to determine the effect of using the Problem Based Learning (PBL) learning model on increasing students' learning motivation on the material of a two-variable linear equation system. The subjects in this study were students of class VIII A of SMP Negeri 4 Tasik Putri Puyu. The object of this research is the Problem Based Learning model to increase students' learning motivation with the material of a two-variable linear equation system. The instruments used are observation sheets, questionnaires and tests. This research was carried out in two cycles, where each cycle consisted of two meetings and one cycle test, each cycle consisting of 4 main activities, namely planning, action, observation, and reflection. From the results of the study, it was found that there was an increase in students' learning motivation by using the Problem Based Learning (PBL) model on the material of a two-variable linear equation system. The results showed that the motivation of students has increased. This can be seen from the average value in the first cycle, which is 96.79 in the medium category, increasing in the second cycle to 108.5 in the high category. So it can be concluded that learning using the Problem Based Learning (PBL) model can increase students' learning motivation on the material of a two-variable linear equation system in class VIII A of SMP Negeri 4 Tasik Putri Puyu